2021
DOI: 10.1001/jamacardio.2020.6909
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Cardiac Fibrosis in Young Adults With a Homozygous Frameshift Variant in SERPINE1

Abstract: IMPORTANCECardiac fibrosis is exceedingly rare in young adults. Identification of genetic variants that cause early-onset cardiomyopathy may inform novel biological pathways. Experimental models and a single case report have linked genetic deficiency of plasminogen activator inhibitor-1 (PAI-1), a downstream target of cardiac transforming growth factor β, with cardiac fibrosis. OBJECTIVE To perform detailed cardiovascular phenotyping and genotyping in young adults from an Amish family with a frameshift variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…SERPINE1, encoding plasminogen activator inhibitor 1 (PAI-1), is an essential inhibitor of tissue plasminogen activator and urokinase (uPA). Previous studies have focused on the effect of SERPINE1 on human thrombosis, cardiac fibrosis, inflammatory injury, ageing and metabolism ( 53 57 ). However, current studies report on the importance of SERPINE1 in promoting tumor malignant progression, distant metastasis and chemotherapy resistance through multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…SERPINE1, encoding plasminogen activator inhibitor 1 (PAI-1), is an essential inhibitor of tissue plasminogen activator and urokinase (uPA). Previous studies have focused on the effect of SERPINE1 on human thrombosis, cardiac fibrosis, inflammatory injury, ageing and metabolism ( 53 57 ). However, current studies report on the importance of SERPINE1 in promoting tumor malignant progression, distant metastasis and chemotherapy resistance through multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…SERPINE1 encodes plasminogen activator inhibitor-1 (PAI-1), a downstream target of heart-transforming growth factor β, which is associated with cardiac fibrosis 30 . Studies showed that a hyperosmotic, autosomal recessive cardiac fibrosis phenotype was found in young adults with homozygous migration variants of SERPINE1, suggesting that cardiac homeostasis requires an optimal range of levels of PAI-1 30 . PAI-1 is elevated in obese people with type 2 diabetes and may contribute to increased cardiovascular disease risk independently of traditional factors 31 .…”
Section: Discussionmentioning
confidence: 99%
“…MIF has been shown to promote the adhesion of leukocytes in general and T cells specifically to endothelial cells. 61 , 62 , 63 SERPINE1 has been associated with cardiac fibrosis, 64 and excessive PAI-1 levels contribute to the accumulation of collagen and other extracellular matrix proteins. This could be of potential importance in the transition from acute cellular rejection to cardiac allograft vasculopathy.…”
Section: Discussionmentioning
confidence: 99%